Ответ:
Пользуемся основными тригонометрическими тождествами:
[tex]sin^2x+cos^2x=1\ \ ,\ \ tgx\cdot ctgx=1\ \ ,\ \ tgx=\dfrac{sinx}{cosx}[/tex] .
[tex]a)\ \ sina\cdot cosa\cdot tga=sina\cdot cosa\cdot \dfrac{sina}{cosa}=sin^2a\\\\\\b)\ \ \underbrace{tgx\cdot ctgx}_{1}-cos^2x=1-cos^2x=sin^2x\\\\\\c)\ \ (1-cosa)(1+cosa)=1-cos^2a=sin^2a\\\\\\d)\ \ \dfrac{sin^2a\cdot ctg^2a}{1-sin^2a}=\dfrac{sin^2a\cdot ctg^2a}{cos^2a}=\dfrac{sin^2a}{cos^2a}\cdot ctg^2a=tg^2a\cdot ctg^2a=1[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пользуемся основными тригонометрическими тождествами:
[tex]sin^2x+cos^2x=1\ \ ,\ \ tgx\cdot ctgx=1\ \ ,\ \ tgx=\dfrac{sinx}{cosx}[/tex] .
[tex]a)\ \ sina\cdot cosa\cdot tga=sina\cdot cosa\cdot \dfrac{sina}{cosa}=sin^2a\\\\\\b)\ \ \underbrace{tgx\cdot ctgx}_{1}-cos^2x=1-cos^2x=sin^2x\\\\\\c)\ \ (1-cosa)(1+cosa)=1-cos^2a=sin^2a\\\\\\d)\ \ \dfrac{sin^2a\cdot ctg^2a}{1-sin^2a}=\dfrac{sin^2a\cdot ctg^2a}{cos^2a}=\dfrac{sin^2a}{cos^2a}\cdot ctg^2a=tg^2a\cdot ctg^2a=1[/tex]